Redesigning a Circular Business Model Canvas (CBMC) for smallholder dairy farming: Financial feasibility and SDG alignment in Sarangan, Indonesia - Yuni K, Kusnul Ciptanila; Hidayat, Nurul; Musfiroh, Anita (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
The Indonesian government has committed to implementing a circular economy, as outlined in its national roadmap to 2025. This study aims to redesign a Circular Business Model Canvas (CBMC) for smallholder dairy farming in Sarangan, Magetan, to enhance farmers’ income and welfare while promoting environmental sustainability. An exploratory mixed-methods design was employed, combining thematic analysis and expert judgment with financial feasibility assessment using the Benefit–Cost (B/C) ratio. The redesigned CBMC incorporates circular economy principles into dairy operations, emphasizing eco-conscious value propositions, diversified revenue streams, and multi-stakeholder partnerships. The results show that cheese processing, yogurt production, and the tourism café are financially viable under normal (B/C ≈ 2.4–2.5) and peak demand (B/C > 6) conditions but not under low-demand conditions (B/C < 1). The model also contributes significantly to the Sustainable Development Goals (SDGs), particularly SDG 8 (Decent Work and Economic Growth, 85%), SDG 6 (Clean Water and Sanitation, 80%), and SDG 7 (Affordable and Clean Energy, 75%), with lower contributions to SDG 12 (70%) and SDG 15 (60%). Key challenges include farmer resistance to adopting new practices, limited access to capital, and seasonal fluctuations in demand. The study addresses these barriers and offers strategies to ensure scalability. Overall, this research fills a gap in the application of circular business models in agrifood systems by integrating business model redesign, financial feasibility, and SDG mapping, providing a replicable framework for smallholder dairy–ecotourism communities in developing regions.